INFOGRAPHICS RELEVANT SOFTWARE USED FOR BUILDING SERVICES DESIGN - Alina FILIP; Silviu GHEORGHE; Gratiela-Maria TARLEA (Journal of Industrial Design and Engineering Graphics, 2024)
The authors present relevant and widely used software for designing building services-HVAC, architectural and electrical installations. Thunderhead PyroSim, Thunderhead Ventus, Bentley AutoPIPE, Kelton Engineering FLOCALC, Bentley OpenBuildings Designer, Bentley OpenFlows HAMMER, WaterCAD, WaterGEMS, SST Systems Caepipe, Graitec ArchiWIZARD, Graitec CADKON, Autodesk AutoCAD, Autodesk FormIt Pro, Vent-Calc, Avenir LoopCAD, Avenir HeatCAD, ISOVER Tech Calc, Energy Soft Energy Pro, Fluid Desk Coolpack are compared, and some examples are given. For a better understanding some simullations are done. The advantages and conclusions are relevant for 2023-2024 Software Generation.